Oral Exposure to Tributyltin Induced Behavioral Abnormality and Oxidative Stress in the Eyes and Brains of Juvenile Japanese Medaka (Oryzias latipes) - Yanhong Shi (MDPI AG, 2021)
The widely used compound tributyltin (TBT), which can be continuously detected in aquatic species and seafood, may induce diverse adverse effects on aquatic organisms. However, little is known regarding the mechanistic links between behavioral abnormality and oxidative stress in different fish tissues in response to oral TBT exposure. Herein, juvenile Japanese medaka (Oryzias latipes) were orally exposed to TBT at 1 and 10 ng/g-bw/d for four weeks. After exposure, the locomotor activity and social interaction of juvenile medaka were found to be significantly reduced in the 10 ng/g-bw/d TBT-exposed group. Furthermore, the antioxidant biomarkers in different tissues of juvenile medaka showed different levels of sensitivity to TBT exposure. The eye superoxide dismutase (SOD) activities markedly increased in both groups exposed to 1 and 10 ng/g-bw/d TBT, while the eye and brain malondialdehyde (MDA) levels increased in the higher dose group. Furthermore, the eye and brain ATPase activities markedly declined in the 1 ng/g-bw/d TBT-exposed group. A correlation analysis revealed that the decreased locomotor activity and social interaction in medaka were associated with the eye antioxidant enzyme (i.e., SOD and catalase (CAT)) activity and brain oxidative damage level. Thus, our findings suggested that there might be some mechanistic links between the behavioral abnormality induced by TBT exposure and oxidative stress in the eyes and brains of medaka. Thus, our findings indicate that the impacts of oral exposure to TBT should be considered to better assess its risk to the aquatic ecosystem and human health.